KEMAMPUAN MENULIS RESENSI KARYA FIKSI SISWA KELAS VIII SMP NEGERI 10 KENDARI - Rinda Inggrit; Amirudin Rahim; La Ode Syukur (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
This research aims to describe students' abilities in writing reviews of works of fiction for class VIII SMP Negeri 10 Kendari. The method used in this research is a quantitative descriptive method. The sampling technique used Proportional Stratified Random Sampling, namely 92 students consisting of five classes. To obtain data about the ability to write reviews of works of fiction, the instrument used in this research is needed, namely a written test. Individually, there were 23 students (25%) who were in the capable category and 69 students (75%) were in the unable category to write reviews of works of fiction. What can be concluded classically is that class VIII students at SMP Negeri 10 Kendari are in the category of not being able to write reviews of works of fiction. It is said that they are not yet capable because individually students have not reached the Learning Completeness Criteria (KKTP) of 66% (25%) and have reached the classical completeness criteria of 85%. Judging from the level of student ability in each aspect of the assessment, namely the identity of the short story (100%), the character of the story (98.91%), the nature of the character (68.47%), the setting of the place (53.26%), the setting of the time (91.30%), background atmosphere (35.86%), theme (68.47%), storyline (%), student opinions (%), reviewer assessment (5.43%), words that contain connotative meanings and denotation (3.26%). Of the total aspects assessed, eight aspects were included in the deficient category because classically the percentage did not reach the Classical Achievement Criteria of 85%.